Neurotransmitter amines and antioxidant agents in neuronal protection against methylmercury-induced cytotoxicity in primary cultures of mice cortical neurons - Olguin, Nair Temis (2018)
Methylmercury (MeHg) is an environmental toxicant with detrimental effects on the developing brain and adult nervous system. The main mechanisms identified include oxidative stress, changes in intracellular calcium, mitochondrial changes, inhibition of glutamate uptake, of protein synthesis and disruption of microtubules. However, little is known about mechanisms of protection against MeHg neurotoxicity. We found that resveratrol (10 μM) and ascorbic acid (200 μM) protected MeHg-induced cell death in primary cultures of cortical neurons. In this work, we aimed at finding additional targets that may be related to MeHg mode of action in cell toxicity with special emphasis in cell protection. We wonder whether neurotransmitters may affect the MeHg effects on neuronal death. Our findings show that neurons exposed to low MeHg concentrations exhibit less mortality if co-exposed to 10 μM dopamine (DA). However, DA metabolites, HVA (homovanillic acid) and DOPAC (3,4-dihydroxyphenylacetic acid) are not responsible for such protection. Furthermore, both DA D1 and D2 receptors agonists showed a protective effect against MeHg toxicity. It is striking though that DA receptor antagonists SKF83566 (10 μM) and haloperidol (10 μM) did not inhibit DA protection against MeHg. In addition, the protective effect of 10 μM DA against MeHg-induced toxicity was not affected by additional organochlorine pollutants exposure. Our results also demonstrate that cells exposed to MeHg in presence of 100 μM acetylcholine (ACh), show an increase in cell mortality at the “threshold value” of 100 nM MeHg. Finally, norepinephrine (10 μM) and serotonin (20 μM) also had an effect on cell protection. Altogether, we propose to further investigate the additional mechanisms that may be playing an important role in MeHg-induced cytotoxicity.